Safety of Fixed Dose of Antihypertensive Drug Combinations Compared to (Single Pill) Free-Combinations: A Nested Matched Case–Control Analysis. Issue 49 (December 2015) - Nowak, Emmanuel; Happe, André; Bouget, Jacques; Paillard, Francois; Vigneau, Cécile; Scarabin, Pierre-Yves; Oger, Emmanuel
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: To compare serious adverse events of fixed-dose dual antihypertensive drug combination (FIXED) to component-based free-combination (FREE). A population-based nationwide cohort from the French Health Insurance System included subjects over 50 years with first time claims (new user) in the second half of 2009 for a calcium-channel blocker or a thiazide-like diuretic in combination with either an angiotensin-converting enzyme inhibitor or an angiotensin receptor blocker as FREE or FIXED. We designed a nested matched case–control analysis with 304 cases, hospitalized for hypotension, syncope, or collapse (n = 224), renal failure (n = 19), hyponatremia, hyper- or hypokalemia (n = 61) and 1394 controls matched for gender, age, date of inclusion in the cohort, and administrative county. Subjects with a medical history of cardiovascular disease, chronic renal failure, or cancer were excluded. The mean age ± SD was 73 ± 10 years and 70% were women. Based on the last delivery preceding the index date, 1414 patients (83%) were exposed to FIXED. Homogeneity of FIXED effect compared to FREE across components of the main composite outcome was rejected ( P  = 0.0099). FIXED formulation significantly increased the odd of the most frequent component (ie, hypotension, syncope, or collapse): OR = 1.88 (95% CI: 1.15–3.05) compared to FREE after adjusting for confounding factors including dose. Serious adverse event occurring in the early phase of treatment deserves attention of physicians because it could alter the benefit/risk ratio of antihypertensive drug combination.